Gaia Space Mission and Quasars - Zwitter, Tomaž (Frontiers in Astronomy and Space Sciences, 2017)
Quasars are often considered to be point-like objects. This is largely true and allows for an excellent alignment of the optical positional reference frame of the ongoing ESA mission Gaia with the International Celestial Reference Frame. But presence of optical jets in quasars can cause shifts of the optical photo-centres at levels detectable by Gaia. Similarly, motion of emitting blobs in the jet can be detected as proper motion shifts. Gaia's measurements of spectral energy distribution for around a million distant quasars is useful to determine their redshifts and to assess their variability on timescales from hours to years. Spatial resolution of Gaia allows to build a complete magnitude limited sample of strongly lensed quasars. The mission had its first public data release in September 2016 and is scheduled to have the next and much more comprehensive one in April 2018. Here we briefly review the capabilities and current results of the mission. Gaia's unique contributions to the studies of quasars are already being published, a highlight being a discovery of a number of quasars with optical jets.